Structure optimization of cam executive component and analysis of precisely applying deep-fertilization liquid fertilizer - Zhou, Wenqi; Wang, Jinwu; Tang, Han (International Journal of Agricultural and Biological Engineering, 2019)
Since there are some problems in the previous cam of deep-fertilization liquid fertilizer applicator, such as poor precision and low-fertilization performance, a method of the contour line of a cam was proposed based on Matlab GUI development platform. Bernoulli’ equation between the liquid fertilizer and the pressure valve of the fertilizer-spraying needle was founded. Moreover, the motion angles of a rise travel and return travel were corrected and the corresponding parameters of the contour line of the cam were obtained. Equations of cam moving from rise travel to return travel were derived according to the simple harmonic motion. In addition, 3D model of cam was established by applying the Pro/E software and the rationality of the cam design was verified. The static analysis of the cam was carried out under working conditions and the corresponding dynamics analysis was performed based on D’Alembert’s principle. And then relationships between the binding force and the drag torque were obtained. A bench test indicates that when the pressure of a hydraulic pump is 0.5 MPa and the velocity of a output shaft is 50 r/min, the average consumption of the fertilizer is 19.7 mL for each measurement, which meets the corresponding agronomic requirement, i.e. 20 mL. When the rotation angle of the cam is 8.6° and the rise displacement of a plunger is 0.84 mm, the mouth of the fertilizer-spraying needle sprayed liquid fertilizer as soon as it got into the soil and stopped spraying as soon as it got out of the soil. The results show that the designed contour line of the cam meets the requirement, that is, the mouth of the fertilizer-spraying needle should spray liquid fertilizer as soon as it gets into the soil and stop spraying as soon as it gets out of the soil, which meets the agronomic requirements, that is, fertilizer should be sprayed deeply and precisely. And this study lays a theoretical foundation for designing the cam of intermittent type distributor and provides relevant parameters.Keywords: liquid fertilizer applicator, cam, precision and deep fertilization, Bernoulli’ equation, D’Alembert’s principle, Matlab, test, optimizationDOI: 10.25165/j.ijabe.20191204.4865Citation: Zhou W Q, Wang J W, Tang H. Structure optimization of cam executive component and analysis of precisely applying deep-fertilization liquid fertilizer. Int J Agric & Biol Eng, 2019; 12(4): 104–109.